How to distance learners like to learn? shared learning preferences in distance education - Botor, N.J.B. (2003)
The study explored what the learning preferences of distance learners are. To achieve this goal, a Q-set, comprised of 52 items representing earlier models and definitions of learning styles, was developed by sampling meaningful words and phrases from learning style and distance education literatures. The distance learners preference for flexibility and convenience; interactive but structures preference for module; goal orientation and non-preference for clutter. Beyond exploring the consensus and disagreements among distance diverse learning preferences could be. This poses a challenge among distance educators and distance education administrations to ensure the learning preferences of distance learners enrolled in the academic programs are appraised and that information gathered from their appraisals are used to inform course development and decision-making. On the other hand, distance learners' awareness of own and others' preferences is contributory to consciously responding to the academic demands of distance education.
Keywords: Distance education; Learning